The two apicomplexa Besnoitia besnoiti and Toxoplasma gondii fifferentially after intrinsic host cell polarity by manipulating centrosome and Golgi apparatus - Cardoso, R. (2015)
Obligate intracellular parasites have co-evolved with hosts to be able to invade their cells and flourish. To be successful they need to establish specific molecular parasite-host cell interactions and then manipulate the host cell structures, mechanisms and pathways in order to replicate and grow. In previous work, we described that upon interaction with the host cell, the apicomplexan Besnoitia besnoiti undergoes dramatic modifications of shape and surface, as revealed by atomic force microscopy, accompanied by a distinct tubulin labeling on the posterior region. In the host cell, the microtubule cytoskeleton shows a re-arrangement around the parasitophorous vacuole (PV). This phenomenon was also observed in the closely related parasite Toxoplasma gondii. During this event, our data suggest that this parasite modulates the levels of tubulin polyglutamylation by controlling the factors that regulate the levels and pattern of tubulin post-translation modifications namely TTLLs, CCPs and severing microtubule enzymes such as spastin, katanin and fidgitin. Also, we have observed that T. gondii recruits the host cell centrosome towards the PV, whereas B. besnoiti does not. Notably, both parasites recruit the host Golgi apparatus to the PV but its organization is differentially affected. Moreover, T. gondii replication rate decreases in cells over-expressing TBCCD1 but not in TBCCD1 depleted cells, while for B. besnoiti no differences were found. However, B. besnoiti promotes a reorganization of the Golgi ribbon previously fragmented by TBCCD1 depletion. In fact, as described by us, TBCCD1 is involved in centrosome positioning and Golgi apparatus integrity Furthermore, the T. gondii tubulin cofactor B (TBCB) gene, a member of tubulin folding pathway that also controls microtubule dynamics through the recycling/degradation of the native tubulin heterodimers is involved in the invasion process of T. gondii. Taken together our results strongly support the importance that a successful establishment of the PVs in the host cell requires a cross-talk between the parasite and the host cytoskeleton through the regulation of the factors that control cytoskeleton specific functions and dynamics. Lastly, the differences found in how T. gondii and B. besnoiti interact with their host cells may indicate different evolutionary paths.